Prophecy in the ancient Near East : a philological and sociological comparison - Stökl, Jonathan, 1977- (Culture and History of the Ancient Near East, 2012)
Since the 1990s there has been an emphasis on the study of ancient Israelite prophecy in its ancient Near East context. Prophecy in the Ancient Near East is the first book-length study that compares prophecy in the ancient Near East by focusing on texts from Mari, the Neo-Assyrian State Archives, and the Hebrew Bible. The author analyzes prophecy in each culture independently before comparisons are made. This method demonstrates how prophecy is a part of the wider system of divination, but also shows where scholarship has unduly imported concepts found in one corpus to the other two. This method, for example, calls into question the supposed link between music and prophecy from the Hebrew Bible to the ancient Near East. This work provides an up-to-date analysis of ancient Near Eastern, including Israelite and Judean, prophecy to scholars and students alike. \'I thoroughly enjoyed reading the book, and I can highly recommend it to anyone interested in prophecy in Israel and the ancient Near East.\' Lena-Sofia Tiemeyer, University of Aberdeen, Review of Biblical Literature \'The content of Jonathan Stökl's book...testifies to the value of the book for the studies of prophecy in the ancient Near East.\' Wojciech Pikor, John Paul II Catholic University of Lublin, The Biblical Annals